Museum Communication: A Conceptual Study - Musiana Yudhawasthi, Ciwuk; Agustini Damayani, Ninis; Yusup, Pawit M.; Suryana, Asep (Opción, 2019)
The main purpose of museum management was to form knowledge which could be achieved through appropriate communication. Museum could act as communication tool for public, both through non-exhibition communica- tion and exhibition related communication. Communication could also be conducted verbally and non-verbally. With the advancement of technology and public behavioral change, museum needed to make breakthroughs through various disciplines of science, to construct the owned values, as a way to communicate. There were only a small number of researches that discussed museum from the perspectives of communication. The objective of this paper was to formulate the concept of museum communication from the viewpoint of Communication Science, therefore the researcher conduc- ted literature studies on previous researches and conducted observations in two university museums in Indonesia. The museums were Anatomy Museum of the Faculty of Medicine and Health Sciences Atma Jaya University/Museum Anatomi Fakultas Kedokteran dan Ilmu Kesehatan Universitas Atma Jaya (Museum Anatomi FKIK UAJ) Jakarta and National Education Museum of Indonesia University of Education/Museum Pendi- dikan Nasional Universitas Pendidikan Indonesia (Mupenas UPI) Bandung to obtain the picture of a communication process. This research was the first stage of the research that aimed to analyze the theory and practices of com- munication in museums.